Oleoylethanolamine and palmitoylethanolamine modulate intestinal permeability in vitro via TRPV1 and PPARα. Issue 2 (13th September 2016) - Karwad, Mustafa A.; Macpherson, Tara; Wang, Bo; Theophilidou, Elena; Sarmad, Sarir; Barrett, David A.; Larvin, Michael; Wright, Karen L.; Lund, Jonathan N.; O'Sullivan, Saoirse E.
ABSTRACT: Cannabinoids modulate intestinal permeability through cannabinoid receptor 1 (CB1). The endocannabinoid‐like compounds oleoylethanolamine (OEA) and palmitoylethanolamine (PEA) play an important role in digestive regulation, and we hypothesized they would also modulate intestinal permeability. Transepithelial electrical resistance (TEER) was measured in human Caco‐2 cells to assess permeability after application of OEA and PEA and relevant antagonists. Cells treated with OEA and PEA were stained for cytoskeletal F‐actin changes and lysed for immunoassay. OEA and PEA were measured by liquid chromatography‐tandem mass spectrometry. OEA (applied apically, logEC50 25.4) and PEA (basolaterally, logEC50 24.9; apically logEC50 25.3) increased Caco‐2 resistance by 20–30% via transient receptor potential vanilloid (TRPV)‐1 and peroxisome proliferator‐activated receptor (PPAR)‐a. Preventing their degradation (by inhibiting fatty acid amide hydrolase) enhanced the effects of OEA and PEA. OEA and PEA induced cytoskeletal changes and activated focal adhesion kinase and ERKs 1/2, and decreased Src kinases and aquaporins 3 and 4. In Caco‐2 cells treated with IFNg and TNFa, OEA (via TRPV1) and PEA (via PPARα) prevented or reversed the cytokine‐induced increased permeability compared to vehicle (0.1% ethanol). PEA (basolateral) also reversed increased permeability when added 48 or 72 h after cytokines (P <0.001, via PPARα). Cellular and secreted levels of OEA and PEA (P <0.001–0.001) were increased in response to inflammatory mediators. OEA and PEA have endogenous roles and potential therapeutic applications in conditions of intestinal hyperpermeability and inflammation.—Karwad, M. A., Macpherson, T., Wang, B., Theophilidou, E., Sarmad, S., Barrett, D. A., Larvin, M., Wright, K. L., Lund, J. N., O'Sullivan, S. E. Oleoylethanolamine and palmitoylethanolamine modulate intestinal permeability in vitro via TRPV1 and PPARα. FASEB J . 31, 469–481(2017). www.fasebj.org